Exploring Psychological and Social Factors Contributing to Family Tensions and Violence Against Married Men by Women: A Qualitative Study - Valian , Ali Mohammad; Gholamzadeh Jofreh , Maryam; Shahbazi , Masoud (Archives of Men's Health, 2024)
Background: Family tensions occur between parents and can be perpetrated by either partner, weakening the family foundation. Domestic violence against men by women is a prevalent yet understudied issue. This qualitative study aimed to explore the psychological and social factors that contribute to domestic violence against men by women. Methods: This qualitative study employed thematic analysis to explore the psychological and social factors contributing to family tensions and violence against married men by women in Iran. Married men who filed domestic violence complaints in Ilam, Iran (2023) participated in purposive group interviews. The recruitment process continued until theoretical saturation was reached, meaning no new themes emerged from subsequent interviews. A total of 16 men participated in the study. Semi-structured interviews with open-ended questions focused on participants' experiences with family tensions and violence. These interviews were audio-recorded with participant consent. Thematic analysis was employed to analyze the collected data, with themes and sub-themes identified and analyzed using MAXQDA 2022 software. Results: Thematic analysis revealed 112 codes, 30 subthemes, and 6 main themes that emerged as the underlying psychological and social factors contributing to domestic violence against men by women in the Iranian context. These main themes were: low psychological resilience, emotional dissatisfaction of the wife, gender role conflict, female chauvinism, marriage based on materialistic goals, and perceived violations of marital vows. Conclusion: Men with low self-esteem and societal pressures on gender roles were more likely to experience domestic violence by their wives. Interestingly, some wives held more power due to their financial or educational status. Materialistic marriages and broken vows further increased the risk of violence. These findings call for a multifaceted approach in Iran, addressing both men's mental health and societal issues, while also creating support systems for male victims.